Factors that Influence Electric Vehicle Purchase Intention: an Evidence from Indonesia - Emiliana Indri Eryolanda; Alim Gunadi Sukanto; Indah Teasari; Andry Mahyudi; Ariyadi Yudo Purnomo; Istijanto Istijanto (Faculty of Economics and Business Udayana University, 2024)
Electric vehicles (EV) are new products that will replace conventional vehicles. Previous studies on factors influencing EVs purchase intention rarely includes the impact of social media factors. This study aims to build a comprehensive model examining factors that influence consumer intention to purchase EVs. Based on the theory of reasoned action and risk-benefit model, this study incorporates social media relevance, vendor trustworthiness, vendor expertise, social influence, and perceptions of EV benefits and risks. Data is collected through online surveys. 295 data were obtained and analyzed by exploratory factor analysis and multiple regression using SPSS. The results show that perceived relevance to social media has the greatest influence on EV purchase intention, followed by perceived benefits and risks, social influence, and vendor expertise, while vendor trustworthiness didn’t have a significant impact. This study’s result contributes to the knowledge of EV buying factors and offers managerial implications for EV providers’ business strategy. Keyword: factor, purchase intention, social media, theory of reasoned action, electric vehicle